Inside the black box of trilogues: introduction to the special issue. Issue 1 (2nd January 2021) - Brandsma, Gijs Jan; Greenwood, Justin; Ripoll Servent, Ariadna; Roederer-Rynning, Christilla
ABSTRACT: This special issue brings together seven original contributions on actors involved in trilogue negotiations whose role has largely been neglecled: the Commission, the Council, the Court, the Ombudsman, national parliaments, organised interests and Eurosceptic groups. This introduction outlines the setup and work processes of trilogues, and highlights the key findings of the issue's contributions, namely how actors at the edge of the negotiations can shape power relations in trilogues and how micro-behaviour shapes macro-processes of inter-institutional bargaining. It also discusses the ongoing tension between transparency and efficiency, notably when it comes to institutional oversight mechanisms and the legitimacy of trilogues.